Endoscopic resection of mucosa and dissection of submucosal layer at early stomach cancer - S. V. Kashin; R. O. Kuvayev; Ye. L. Zakrevskaya; D. V. Zav’yalov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present possible management approach for patients with early stomach cancer.Original positions. Nowadays morbidity and mortality due to stomach cancer still occupies the leading positions all over the world. The main way to decrease its prevalence is diagnostics and well-timed treatment of preneoplastic states, first of all – chronic atrophic gastritis associated to Helicobacter pylori infection. Revealing of stomach cancer at early stages and adequate treatment of patients improve the prognosis. Screening diagnostics of the asymptomatic population and investigation of risk groups are efficient approaches in detection of early stomach cancer. Of all diagnostic methods high quality endoscopic investigation is considered to be the most effective. The important stage of management of patients with early stomach cancer is endoscopic resection of tumor. In the last years in practice of clinics in many countries of the world new procedure – endoscopic submucosal resection began to be introduced widely.